Cultural adaptation of the caas: Measuring career adaptability among vocational high school students - Sari, Arlina; Sugiharto, Dwi Yuwono Puji Sugiharto; Sunawan (Universitas Islam Negeri Raden Intan Lampung, 2025)
Assessing the CAAS among VHS students provides insights into the students' career adaptability concerning the transition from VHS to the workforce. While the CAAS is used concerning students' adaptability within the VHS curriculum, there is a lack of development of an appropriate and validated indonesian version of the CAAS for VHS students. The CAAS consists of the core dimensions of concern, control, curiosity, and confidence. This study sought to culturally adapt the CAAS, develop its validation, and assess the reliability of the CAAS within an educational context, with the CAAS focused specifically on VHS students. The sample consisted of 396 students from 9th and 10th grade. Data were analysed using CFA and multigroup invariance testing. Internally, the CAAS dimensions achieved distributive achievement of CAAS dimensions and contained acceptable convergent reliabilities. However, there were some CAAS dimensions which contained low AVEs. However, the model fit indices, achieving 0.943 and an RMSEA of 0.056, suggest a good model fit. In particular, multigroup invariance testing, which obtained configurational, metric, scalar, and strict invariance, further strengthened the index and model fit testing. With proven validation and reliability, the Indonesian version of the CAAS measures the career adaptability of vocational high school students; this demonstrates its value for vocational schools in developing sharper career guidance for students. Considering other variables related to career development, future studies should focus on predictive validity and other educational levels. Further research should assess the predictive validity with other career development variables and extend to other educational levels.